Expression of a Codon-Optimized dsdA Gene in Tobacco Plastids and Rice Nucleus Confers D-Serine Tolerance - Li, Yanmei; Wang, Rui; Hu, Zongliang; Li, Hongcai; Lu, Shizhan; Zhang, Juanjuan; Lin, Yongjun; Zhou, Fei (Frontiers in Plant Science, 2016)
D-serine is toxic to plants. D-serine ammonia lyase, which is encoded by the dsdA gene, can attenuate this toxicity with high specificity. In the present study, we explored the function of codon-optimized dsdA with tobacco plastids and rice nuclear transformation system. It was shown that the dsdA gene was site-specifically integrated into the tobacco chloroplast genome and displayed a high level of expression. Genetic analysis of the progenies showed that the dsdA gene is maternally inherited and confers sufficient D-serine resistance in tobacco. The effective screening concentrations of D-serine for seed germination, callus regeneration and foliar spray were 10 mM, 30 mM and 75 mM, respectively. In addition, calluses from homozygous transgenic rice lines also showed significant tolerance to D-serine (up to 75 mM). Our study proves the feasibility of using dsdA gene as a selectable marker in both chloroplast and nuclear transformation systems.